2019
DOI: 10.1523/eneuro.0457-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Postmeal Optogenetic Inhibition of Dorsal or Ventral Hippocampal Pyramidal Neurons Increases Future Intake

Abstract: Memory of a recently eaten meal can serve as a powerful mechanism for controlling future eating behavior because it provides a record of intake that likely outlasts most physiological signals generated by the meal. In support, impairing the encoding of a meal in humans increases the amount ingested at the next eating episode. However, the brain regions that mediate the inhibitory effects of memory on future intake are unknown. In the present study, we tested the hypothesis that dorsal hippocampal (dHC) and ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 132 publications
6
29
0
Order By: Relevance
“…Some reports indicate the involvement of the ventral hippocampus in models of feeding behavior using high concentrations of sucrose. Data from these experiments show that inhibition of ventral hippocampus function after concluding a meal increases feeding at the next meal (Hannapel et al 2019;Hannapel et al 2017), a finding broadly consistent with the data presented in this report. Thus, more work needs to be done to determine the role of the ventral hippocampus on consummatory behavior.…”
Section: Discussionsupporting
confidence: 89%
“…Some reports indicate the involvement of the ventral hippocampus in models of feeding behavior using high concentrations of sucrose. Data from these experiments show that inhibition of ventral hippocampus function after concluding a meal increases feeding at the next meal (Hannapel et al 2019;Hannapel et al 2017), a finding broadly consistent with the data presented in this report. Thus, more work needs to be done to determine the role of the ventral hippocampus on consummatory behavior.…”
Section: Discussionsupporting
confidence: 89%
“…[3,12,13]). We also noted that inhibitory hippocampal modulation of appetite in animals could occur independent of state [24], perhaps paralleling memory-based inhibition effects in people [11]. Returning to the accounts outlined in the Introduction, the incentive salience model was suggested to occur via internal state acting to dampen brain reward circuit activity.…”
Section: Discussionmentioning
confidence: 72%
“…Irrespective of which of these accounts of modulation might be correct, there are grounds for thinking that the hippocampus is involved in using interoceptive state to regulate appetite [11,23]-although noting that inhibitory effects in animals can be obtained seemingly independent of interoceptive state [24]. The hippocampus has an established experimental and theoretical history of involvement in inhibitory processing (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the observed impairments in episodic memory are functionally related to the increased spontaneous meal frequency following VANspecific GHSR knockdown. Lesioning or inhibition of hippocampal neurons reduces the intermeal interval in rodent models, in addition to increasing intake at the next meal [31][32][33][34]. In humans, interfering with meal-related episodic memory (by decreasing perceived food intake while controlling for actual food intake) increases subjects' self-reported hunger rating during the intermeal interval [35], while a separate study showed that simply being asked to recall a previous meal decreases future intake at the subsequent meal [36].…”
Section: Discussionmentioning
confidence: 99%